The Original of Cyrillic Early Printed Tetraevangelia Issued in Pochaiv. Study of Saints and Feasts Present in the Menologia - Ostapczuk, Jerzy (Slavistica Vilnensis, 2023)
Out of 110 early printed Cyrillic liturgical Tetraevangelia, five were issued by the printing house of the Holy Dormition Pochaiv Lavra. All of them appeared in the 2nd half of the 18th century and were intended for the use in the Uniate, i.e., Greek-Catholic, Church. A text critical study of different texts from various parts of Tetraevangelia has suggested that the Gospel edition issued in Kyiv in 1746 was used by printers in Pochaiv to prepare their first liturgical Tetraevangelion. This publication is focused on the textual analysis of menologia present in early printed Cyrillic Tetraevangelia, with particular attention given to the saints and feasts, as well as verbatim correspondence of commemorations and liturgical rubrics. Its results allow to conclude that the first Tetraevangelion issued at the Holy Dormition Pochaiv Lavra in 1759, was prepared on the basis of the Gospel edition issued at the Kyiv Pechersk Lavra in 1746. Liturgical rubrics in the first Pochaiv Tetraevangelion were adjusted to the liturgical tradition of the Greek-Catholic Church. Four further Pochaiv liturgical Gospel editions copied, with some minor corrections, the menologion of the first one.